Diffractive memory-stories and response-activeness in teaching social justice. Issue 6 (2nd November 2022) - Müller, Marguerite; Le Roux, Adré; Kruger, Frans
ABSTRACT: This article presents a diffractive arts-based narrative that results from a re-turn of our work with subjectivity and memory in relation to our involvement with teaching social justice and diversity in education. Through intra-action, we explore the entanglement of subjectivity and memory in working towards different possibilities for more response-active social justice curricula and pedagogy. The concept of nested-time informs our diffractive narrative as we engage with our experiences and becomings in a non-linear and collaborative way. We use the concept of shared responsibility as an intermezzo to memories of discomfort, emotions of guilt, self-doubt, messiness, frustration, and complexity and the way these might help us to think and act differently. The diffractive memory-stories thus create possibilities for response-activeness as we imagine new responses and actions against social injustices and sufferings in our classrooms and in our communities.